THE DYNAMICS OF PESANTREN: Responses toward Modernity and Mechanism in Organizing Transformation (JOURNAL OF INDONESIAN ISLAM, 2011)
The development of pesantren from time to time illustrates its significant role within communities. Its dynamic development appears clearly as a result of its ability to adapt into the external condition. Its communities are well-known with their social skills in dealing with external culture that comes from all types of challenges coming from outside. Pesantren has an internal mechanism to adapt into a new trend, due to the development of its function and differentiation. The empirical experiences show the ability of four imperative functions of pesantren, namely: high ability to adapt into the external world, wide-ranging goal achievement, integrative ability of unifying the unique aspects of pesantren as sub-culture, and ability in preserving the pesantren’s tradition with the principle “maintaining the old good tradition and gaining a new better tradition”. Differentiation mechanism is a gradual transformation process of pesantren that causes the steady increase of new units within it to perform their functions more effectively. This response leads to various models of pesantren.